2019
DOI: 10.1039/c9ta03944a
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-doped Ni–Co phosphides with multiple catalytic sites as efficient electrocatalysts for overall water splitting

Abstract: The design of electrocatalysts including precious and nonprecious metals for the hydrogen evolution reaction (HER) in alkaline media remains challenging due to the sluggish reaction kinetics caused by the additional water dissociation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(80 citation statements)
references
References 55 publications
0
79
0
Order By: Relevance
“…peaks. [41][42][43] Additionally, the the minor peaks at 853.77 and 872.07 eV are attributed to the metallic Ni. 44 Compared with Ni 2 P, the Ni 2p binding energy of P-NiFeP positive shifts of 0.97 eV ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…peaks. [41][42][43] Additionally, the the minor peaks at 853.77 and 872.07 eV are attributed to the metallic Ni. 44 Compared with Ni 2 P, the Ni 2p binding energy of P-NiFeP positive shifts of 0.97 eV ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, NiCoP is derived from NiCo oxide (NiCoO x ) via phosphorus substitution using chemical vapor deposition method, in which the morphology of NiCoP inherits from NiCoO x . [ 18,19,29,45–47 ] Recently, Guo et al reported a general wet‐chemical approach to synthesize large‐size, ultrathin 2D metal oxide nanosheets based on graphene oxide (GO) template, in which the nucleation and growth of metal ions are balanced during hydrolysis to prevent forming precipitates. [ 48 ] Based on this approach, only single‐metal oxide nanosheets with micron‐scale size and several nanometer‐thickness have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter R ct relates to the overall rate in the OER process; a decrease in its value concerning increasing potential represents faster electron transfer kinetics. [56] At 1.54 V vs. RHE, W-doped NiÀ Fe hydroxides show smaller R ct than NiFe, which accounted for fast surface reactions for water oxidation. In the initial overpotential region, NiFeW2 presents the lowest R ct value, 1.56 Ω at 1.464 V vs. RHE, compared to those of NiFeW1 (2.23 Ω) and NiFeW3 (1.76 Ω), indicating accelerated charge transfer between the catalyst and substrate for faster OER kinetics.…”
Section: àmentioning
confidence: 96%